RETRACTED: Activation-induced internalization differs for the tetraspanins CD9 and Tspan8: Impact on tumor cell motility - Rana, Sanyukta; Claas, Christoph; Kretz, Cosima C.; Nazarenko, Irina; Zöller, Margot (International journal of biochemistry & cell biology, 2011)
Exosomes are most important intercellular communicators and tetraspanins/tetraspanin-complexes have been suggested to play an important role in exosomal target cell selection. We have shown that only exosomes expressing a Tspan8-CD49d complex preferentially bind endothelial cells, which initiates angiogenesis. This finding was unexpected as in the exosome donor cell Tspan8 is associated with CD49c and the tetraspanins CD9 and CD151. In view of the discussed therapeutic power of exosomes as message/drug transporter, it became important to clarify the mechanisms accounting for the distinct Tspan8-web in the cell membrane versus exosomes. We therefore compared the route of Tspan8 and Tspan8-chimera internalization, where the N- and/or C-terminal regions were exchanged with the corresponding regions of CD9 or CD151. Activation-induced Tspan8-internalization proceeds more rapidly than CD9 internalization and is accompanied by disassembly of the Tspan8-CD9-CD151 membrane complex in resting cells. Tspan8-internalization relies on the association of the Tspan8 N-terminal region with intersectin-2, a multimodular complex involved in clathrin-coated pit internalization. Internalization and recovery of Tspan8 in early endosomes is further promoted by the recruitment of CD49d such that only in PMA-activated cells a Tspan8-INS2-CD49d-clathrin complex is recovered in cholesterol-depletion-resistant membrane microdomains. PMA-induced Tspan8-internalization promotes cell migration, but reduces matrix and cell adhesion. Thus, stimulation initiates tetraspanin-web rearrangements, which have strong functional consequences for the cell, exosome-delivery and exosome target selection. This knowledge will be essential for generating tailored therapeutic exosomes.